2021
DOI: 10.3389/fenvs.2021.619258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvest and Fertilization Frequency on Protein Yield and Extractability From Flood-Tolerant Perennial Grasses Cultivated on a fen Peatland

Abstract: Paludiculture, and in particular the cultivation of perennial grasses as biomass feedstock for green biorefineries, may be an economic and environmentally sustainable option for agricultural peatlands in temperate regions. However, the optimal biomass quality for protein extraction from flood-tolerant grasses is largely unknown. The aim of this study was to define the combined effect of harvest and fertilization frequency, with one to five annual cuts, on protein yield and extractability for the grasses tall f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…For biorefining, the protein content in grass biomass depends on nitrogen availability, frequency and timing of cutting, similar to the systems on intensive arable land. Recent research found crude protein contents of up to 2.9–3.4 t/ha/year, and precipitated protein concentrates of up to 1.2–2.2 t/ha/year, for reed canary grass and tall fescue, cultivated on wet organic soils (Nielsen, Stødkilde, et al, 2021). Optimal timing of harvest seems to remain the most critical factor for biomass and protein yields.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For biorefining, the protein content in grass biomass depends on nitrogen availability, frequency and timing of cutting, similar to the systems on intensive arable land. Recent research found crude protein contents of up to 2.9–3.4 t/ha/year, and precipitated protein concentrates of up to 1.2–2.2 t/ha/year, for reed canary grass and tall fescue, cultivated on wet organic soils (Nielsen, Stødkilde, et al, 2021). Optimal timing of harvest seems to remain the most critical factor for biomass and protein yields.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to experiments on university experimental farms, research is also performed on farmers' fields; e.g. to analyse crop productivity and protein content, and greenhouse gas balance on lowland organic soils (Kandel et al, 2013, 2016; Nielsen, Elsgaard, et al, 2021, Nielsen, Stødkilde, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With an increasing policy focus on wetland restoration, including paludiculture, for GHG mitigation and nutrient retention, as well as the concomitant need to point out sites with the highest mitigation potential, not only assessments of GHG emissions and optimum management (e.g., Geurts et al, 2019;Tanneberger et al, 2020;Nielsen et al, 2021) but also siteand plant community-specific BGB NPP should be taken into consideration for an accurate evaluation of the C sink potential.…”
Section: T Dm Hamentioning
confidence: 99%
“…While currently an effort is made to review R/S for different biomes and climate zones (e.g., Qi et al, 2019), an assessment of the R/S of grasses under different harvest frequencies is still lacking. This is particularly true for flood-tolerant grass species, which are increasingly introduced on both wetland and upland soils for both climate change mitigation and added-value products, such as grass protein as a substitute for soy (Nielsen et al, 2021). Hence, there is a need for consolidated estimates of R/S for commonly used paludiculture crops under different harvest frequencies (Karki et al, 2014).…”
Section: Introductionmentioning
confidence: 99%